2011
DOI: 10.1007/s12230-011-9203-6
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B1 Content in Potato: Effect of Genotype, Tuber Enlargement, and Storage, and Estimation of Stability and Broad-Sense Heritability

Abstract: Thiamine pyrophosphate (vitamin B 1 ) is an essential nutrient in the human diet, and is often referred as the energy vitamin. Potato contains modest amounts of thiamine. However, the genetic variation of thiamine concentrations in potato has never been investigated. In this study, we determined thiamine concentrations in freshly-harvested unpeeled tubers of 54 potato clones, the majority of them originating from the Pacific Northwest Potato Development Program. Tubers from 39 clones were collected from four d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 36 publications
0
19
1
Order By: Relevance
“…Moreover, the Vitamin C content of potato was lower than that of orange (73 mg 100 g -1 FW), cabbage (42 mg 100 g -1 FW) and tomato (14 mg 100 g -1 FW) (Vanderslice et al 1990), but remarkably higher than that of wheat (0 mg 100 g -1 FW) (Dobladomaldonado et al 2012). The mean content of vitamin B 1 was lower than the levels reported by Goyer and Haynes (2011), whose study showed that the average vitamin B 1 content of the America varieties harvested in 2009 was 0.85 mg kg -1 FW. Studies carried out by Finglas and Faulks (1984) showed that the mean riboflavin content of four maincrop varieties, such as Desiree, King Edward, etc.…”
Section: Vitamins Tpc and Antioxidant Capacitycontrasting
confidence: 65%
“…Moreover, the Vitamin C content of potato was lower than that of orange (73 mg 100 g -1 FW), cabbage (42 mg 100 g -1 FW) and tomato (14 mg 100 g -1 FW) (Vanderslice et al 1990), but remarkably higher than that of wheat (0 mg 100 g -1 FW) (Dobladomaldonado et al 2012). The mean content of vitamin B 1 was lower than the levels reported by Goyer and Haynes (2011), whose study showed that the average vitamin B 1 content of the America varieties harvested in 2009 was 0.85 mg kg -1 FW. Studies carried out by Finglas and Faulks (1984) showed that the mean riboflavin content of four maincrop varieties, such as Desiree, King Edward, etc.…”
Section: Vitamins Tpc and Antioxidant Capacitycontrasting
confidence: 65%
“…As vitamin B 1 is known to be heat sensitive and water soluble ( Fitzpatrick et al , 2012 ), losses are expected to occur during the processing and cooking of cassava storage roots. For example, boiling peeled potatoes for 30 minutes leads to a 12% reduction in vitamin B 1 content ( Augustin et al , 1978 ; Goyer and Haynes, 2011 ). Therefore, we tested whether processing and cooking alters the vitamin B 1 content in cassava leaves and storage roots.…”
Section: Resultsmentioning
confidence: 99%
“…The exploitation of natural variation further assists in the identification of markers for candidate genes that control micronutrient accumulation ( Conn et al , 2012 ), as it has been shown for vitamin A in rice ( Vallabhaneni et al , 2009 ; Yan et al , 2010 ). Diversity of vitamin B 1 content has so far been analyzed only in rice and potato germplasm ( Villareal and Juliano, 1989 ; Sotelo et al , 1990 ; Kennedy and Burlingame, 2003 ; Goyer and Haynes, 2011 ; Goyer and Sweek, 2011 ). Characterization of the diversity of vitamin B 1 accumulation in the germplasm of staple crops could help in the implementation of biofortification approaches to reduce vitamin B 1 deficiencies.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above, with current technologies, mining of the thousands of rice varieties available may reveal cultivars with increased thiamine contents (99), the molecular basis of which could be used to increase endosperm thiamine content in this food crop through engineering or breeding. To date, a set of cassava cultures have been examined for their diversity in vitamin B 1 content (95), as well as a small set of rice and potato cultivars (91,(100)(101)(102). However, only up to 3-fold variation was observed in the varieties analyzed in these studies; thus, further genetic resources remain to be examined for their thiamine content.…”
Section: Thiamine Biofortification In Crops For Human Healthmentioning
confidence: 99%